An evaluation of BEE implementation in small, medium and micro enterprises (SMMES) of the tourism sector : Soweto in South Africa - Zulu, Vincent Nkosinathi (Stellenbosch : Stellenbosch University, 2018)
Thesis (MPA)--Stellenbosch University, 2018.